Plan de supervisión y monitoreo para asegurar la identificación de los beneficiarios del Sistema de Focalización de Hogares Trujillo. 2019 - Sandoval Colala, Ana Mercy (2022)
This research is about “Supervision and Monitoring Plan to ensure the identification of the beneficiaries of the Trujillo Household Targeting System. 2019”. Its purpose is to determine how a supervision and monitoring plan would ensure the identification of the beneficiaries of the Household Targeting System in Trujillo 2019. Surveys were applied to specialists, coordinators or representatives of the Focused Public Interventions, members of the Household Focalization System - SISFOH, in order to know their perception of the service provided. Coming to the conclusion of how important it is to carry out a diagnosis to generate indicators in a SISFOH supervision and monitoring plan, since when analyzing the household targeting system, critical processes that delay the socioeconomic classification of households can be identified potential users of the social programs and subsidies offered by the Peruvian State, research that by its form originates in a diagnosis of the policy of targeting in the country. In addition, it was determined that the follow-up of the processes will allow effective control in a supervision and monitoring plan, since by monitoring, recording and analyzing the teaching processes, deficiencies, obstacles and / or obstacles can be detected in a timely manner. needs which will allow a correct decision making.